2017
DOI: 10.1007/s00167-017-4613-8
|View full text |Cite
|
Sign up to set email alerts
|

Talus bipartitus: a systematic review and report of two cases with arthroscopic treatment

Abstract: Purpose The aim of this study was to provide a literature review on talus bipartitus and to introduce an arthroscopic treatment option.Methods A systematic review of published case reports and small case series was performed. Medline, Embase, CINAHL, Google Scholar and Web of Science databases were searched for relevant publications. In addition, three cases of talus bipartitus treated in our institute were discussed.ResultsEleven articles were identified, reporting on 23 patients, of whom one patient had a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…By contrast, a bipartite talus will involve the posteromedial and posterolateral tubercles of the talus and appear as a much larger bony fragment, with a division occurring within the coronal plane of the talus separating it into anterior and posterior components with both segments having contributions to the articular surface of the ankle joint. 10,11 In this patient, the bone fragment was much more medial and larger than previously documented os trigonums at close to 3 cm on the axial imaging. By contrast, in a retrospective study of foot and ankle axial CT scans of 204 patients with os trigonums, the majority measured less than 1.5 cm.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…By contrast, a bipartite talus will involve the posteromedial and posterolateral tubercles of the talus and appear as a much larger bony fragment, with a division occurring within the coronal plane of the talus separating it into anterior and posterior components with both segments having contributions to the articular surface of the ankle joint. 10,11 In this patient, the bone fragment was much more medial and larger than previously documented os trigonums at close to 3 cm on the axial imaging. By contrast, in a retrospective study of foot and ankle axial CT scans of 204 patients with os trigonums, the majority measured less than 1.5 cm.…”
Section: Discussionmentioning
confidence: 51%
“…7,13 Similar to TTS, the initial treatment of a symptomatic bipartite talus or os trigonum syndrome may begin conservatively with activity modification, rest, and anti-inflammatories, with progression to surgical treatment should conservative management fail. 8,[10][11][12] In this unusual case, we describe an initial TTS presentation in an older patient secondary to a large bony structure within the posterior ankle. This structure, originally thought to be a large os trigonum, was identified as a bipartite talus, which was successfully managed with tarsal tunnel decompression and removal of the posterior talar fragment.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Differential diagnosis of TB includes the presence of an os trigonum, which lacks of articular surface and has a higher incidence (13%). Zwiers et al [ 18 ] identified only 23 reported cases of TB in their systematic review. None of them involved neuropathy entrapment.…”
Section: Discussionmentioning
confidence: 99%